Solid electrolyte membrane and preparation method thereof, solid-state battery and electric device

By using a composite adhesive bonded with polyimide and polytetrafluoroethylene with a specific structure in a solid-state battery, the adhesion between the electrode sheet and the solid-state electrolyte film is improved, and the problem of low battery impedance and conductivity is solved, and the problem of high-voltage resistance and conductivity is improved. The performance and life of the battery.

CN119324248APending Publication Date: 2025-01-17SHENZHEN POWER SUPPLY BUREAU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411338958.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The poor adhesion between the electrode sheet and the solid electrolyte film in a solid-state battery leads to an increase in the battery impedance and a decrease in the conductivity, which affects the safety and life of the battery.

Method used

Polyimide with specific structures is used as a composite binder to combine with lithium-containing solid electrolyte and polytetrafluoroethylene to form a solid electrolyte membrane with high viscosity, flexibility and surfactivity, improving interface contact and ions between electrode materials Transmission efficiency.

Benefits of technology

It effectively reduces the impedance of the battery, improves the conductivity, enhances the adhesion and mechanical strength of the solid electrolyte membrane, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324248A_ABST
    Figure CN119324248A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a solid-state electrolyte membrane and a preparation method thereof, a solid-state battery and an electric device. The solid electrolyte membrane provided by the invention comprises a lithium-containing solid electrolyte and a composite binder in a mass ratio of (99.2-99.9): (0.1-0.8), the composite binder comprises a first binder and a second binder; the first binder comprises polytetrafluoroethylene; the second binder comprises polyimide, and the polyimide has a structural unit as shown in a formula (I). Wherein each R1 is independently a single bond,-O-,-C (= O)-, an ester group, # imgabs 0 #, # imgabs 1 # or # imgabs 2 #; and L1, L2 and L3 are each independently an arylene group with a carbon atom number of 6 to 12. A ring is selected from a structure shown in a formula (A-1) to a formula (A-6), and R2 is independently H, halogen, alkyl with the carbon atom number of 1-8 or halogenated alkyl with the carbon atom number of 1-8 when appearing each time; m is a positive integer greater than or equal to 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte membrane and a preparation method thereof, a solid-state battery, and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, etc. With the development of current society, people have higher and higher requirements for the safety and long life of lithium-ion batteries.

[0003] With the progress of battery research, non-flammable and non-leaking solid-state batteries have emerged. Replacing electrolytes with solid electrolytes in solid-state batteries can greatly improve battery safety and ensure battery energy density. However, in solid-state batteries, there is a problem of poor adhesion between the electrode sheet and the solid electrolyte interface or between the components in the solid electrolyte membrane, which increases the impedance of the battery and reduces the conductivity. Summary of the invention

[0004] Based on this, the present application provides a solid electrolyte membrane and a preparation method, a solid-state battery, and an electrical device. The solid electrolyte membrane provided by the present application has good adhesion between the components and good interface contact with the electrode sheet, which can effectively reduce the impedance of the battery and improve the conductivity.

[0005] In a first aspect of the present application, a solid electrolyte membrane is provided, wherein the solid electrolyte membrane comprises a lithium-containing solid electrolyte and a composite binder in a mass ratio of (99.2 to 99.9): (0.1 to 0.8);

[0006] The composite binder includes a first binder and a second binder; the first binder includes polytetrafluoroethylene;

[0007] The second binder includes polyimide, and the polyimide has a structural unit represented by formula (I): ;

[0008] Wherein, R1 is each independently a single bond, -O-, -C(=O)-, an ester group, , or ; L1, L2 and L3 are each independently an arylene group having 6 to 12 carbon atoms;

[0009] Ring A is selected from the structures represented by formula (A-1) to formula (A-6): , , , , , ; each occurrence of R2 is independently H, a halogen, an alkyl group having 1 to 8 carbon atoms, or a haloalkyl group having 1 to 8 carbon atoms; m is a positive integer greater than or equal to 1.

[0010] In one embodiment, each R1 is independently -C(=O)- or an ester group, and the A ring is or , and each occurrence of R2 is independently an alkyl group having 1 to 8 carbon atoms or a haloalkyl group having 1 to 8 carbon atoms.

[0011] In one embodiment, the polyimide includes , , , , , , , , , , and one or more of.

[0012] In one embodiment, in the composite binder, the mass ratio of the first binder to the second binder is 1:(0.1 - 10).

[0013] In one embodiment, by mass percentage, the solid electrolyte membrane includes: 99.2% - 99.9% of a solid electrolyte, 0.05% - 0.4% of a first binder, and 0.05% - 0.4% of a second binder.

[0014] In one embodiment, the lithium-containing solid electrolyte includes Li n1 PO n2 N n3 and one or more of Li3MeCl6;

[0015] wherein, 0 < n1 ≤ 1, 0 < n2 ≤ 1, 0 < n3 ≤ 1; Me includes one or more of In, Y, Sc, Ta, Zr, Yb, and Ho.

[0016] In one embodiment, the thickness of the solid electrolyte membrane is 15 µm - 200 µm.

[0017] In a second aspect of the present application, there is provided a method for preparing the solid electrolyte membrane according to any one of the first aspect of the present application, including the following steps:

[0018] Mix the lithium-containing solid electrolyte and the composite binder, and after pressing, prepare the solid electrolyte membrane.

[0019] In one embodiment, the preparation method has one or more of the following characteristics:

[0020] (1) The mixing process parameters include: a mixing temperature of 30°C to 100°C;

[0021] (2) The pressing process parameters include: the pressing temperature is 20°C to 200°C.

[0022] According to a third aspect of the present application, a solid-state battery is provided, comprising a positive electrode, a negative electrode, and an electrolyte membrane disposed between the positive electrode and the negative electrode, wherein the electrolyte membrane is the solid-state electrolyte membrane described in any one of the embodiments of the first aspect of the present application.

[0023] The solid electrolyte membrane provided by the present application has at least the following advantages:

[0024] The solid electrolyte membrane provided by the present application includes a lithium-containing solid electrolyte and a composite binder in a specific mass ratio, wherein the composite binder includes a first binder and a polyimide second binder of a specific structure. The polar groups such as the imide group contained in the polyimide can interact with the ions in the lithium-containing solid electrolyte to promote the dissolution and transmission of the ions; at the same time, it can also enhance the interfacial bonding force between the polyimide and the pole piece, and improve the transmission efficiency of the ions at the interface. In addition, the conjugated structure contained in the polyimide and the spatial configuration of the functional group can provide a more favorable channel for ion transmission and reduce the resistance to ion transmission.

[0025] Therefore, a polyimide with a specific molecular structure is selected, which can generate a strong intermolecular force between the lithium-containing solid electrolyte and the first binder, thereby improving the viscosity of the solid electrolyte membrane. At the same time, polyimide has certain flexibility, deformability and surface activity, which can better fill and fit the gaps between different materials and improve the interfacial wettability between the solid electrolyte and the electrode material, so as to reduce interfacial voids and defects, increase the interfacial contact area, enhance the bonding effect, enhance the ion transmission efficiency and reduce the transmission impedance. In addition, the polyimide compounded with the first binder can also provide a certain mechanical strength and stability for the solid electrolyte membrane, thereby preventing the solid electrolyte from structural damage or deformation during the charge and discharge process.

[0026] In summary, the solid electrolyte membrane provided in the present application can effectively improve the adhesion between the components of the solid electrolyte membrane and between the components and the electrode sheets by selecting a polyimide with a specific structure, and in combination with a lithium-containing solid electrolyte and a first binder, so as to form a good enhanced interface contact; thereby, it can effectively reduce the impedance of the battery and improve the conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1This is an impedance test diagram after the solid electrolyte membranes of Example 1, Comparative Example 1 and Comparative Example 2 of the present application are assembled into solid-state batteries;

[0028] Figure 2 Actual photos of the dry-process electrolyte membranes prepared in Example 1 and Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0029] The following is a further complete and clear description of the solid electrolyte membrane and preparation method, solid-state battery, and electrical device of the present application in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0030] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. Unless otherwise specified or there is a contradiction, the terms or phrases used herein have the following meanings:

[0032] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0033] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0035] In the present application, references to “combinations thereof”, “any combination thereof”, “any combination thereof”, etc. include all suitable combinations of any two or more of the listed items.

[0036] In this application, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc. shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0037] In the present application, the terms “preferred”, “better”, “more preferred” and “suitable” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present application.

[0038] In the present application, the terms “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0039] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0040] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.

[0041] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0042] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0043] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0044] In the present application, "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. Phrases containing this term, for example, "aryl having 6 to 12 carbon atoms" refers to an aromatic group containing 6 to 12 atoms, and each occurrence can be independently C6 aryl or C10 aryl. Suitable examples include, but are not limited to, benzene and naphthalene.

[0045] The "arylene group" refers to an aromatic hydrocarbon group derived from an "aryl group" by removing a hydrogen atom.

[0046] The term "alkyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. A phrase containing this term, for example, "alkyl having 1 to 8 carbon atoms" refers to a straight or branched chain alkyl having 1 to 10 carbon atoms, and each occurrence may be independently C1 chain alkyl, C2 chain alkyl, C3 chain alkyl, C4 chain alkyl, C5 chain alkyl, C6 chain alkyl, C7 chain alkyl, C8 chain alkyl. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(C H3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (- CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH( 2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).

[0047] As used herein, "halogen" or "halo" refers to -F, -Cl, -Br or -I.

[0048] "Haloalkyl" refers to an alkyl group substituted with one or more halogen (chlorine, fluorine, bromine or iodine) atoms. Polyhaloalkyl groups have the same or mixed types of halogen atoms. "Perhaloalkyl" refers to an alkyl group in which each hydrogen atom is replaced by a halogen atom. A haloalkyl group that is "fully halogenated" at a particular carbon atom means that all hydrogen atoms attached to that carbon are replaced by halogen atoms. Representative mono-, di- and trihaloalkyl groups include: chloromethyl, chloroethyl, bromomethyl, bromoethyl, iodomethyl, iodoethyl, chloropropyl, bromopropyl, iodopropyl, 1,1-dichloromethyl, 1,1-dibromomethyl, 1,1-dichloropropyl, 1,2-dibromopropyl, 2,3-dibromopropyl, 1-chloro-2-bromoethyl, 2-chloro-3-bromopropyl, trifluoromethyl, trichloromethyl, and the like.

[0049] In this application, "*" or " " represents a connection site or a fusion site. In the present application, when a connection site is not specified in a group, it means that an optional connection site in the group is used as a connection site; in the present application, when a fusion site is not specified in a group, it means that an optional fusion site in the group is used as a fusion site, and preferably two or more sites in adjacent positions in the group are fusion sites.

[0050] In the present application, when a linking site is not specified in a group, it means that an optional linking site in the group can be used as a linking site.

[0051] In the present application, the single bond to which the substituent is connected runs through the corresponding ring, indicating that the substituent can be connected to any position of the ring, for example R is connected to any substitutable position of the benzene ring.

[0052] Since solid-state batteries use solid electrolytes instead of organic electrolytes, which effectively avoids safety hazards such as leakage of traditional lithium-ion batteries and has a higher energy density, solid-state batteries are expected to become one of the most important energy storage devices of the next generation. However, solid-state batteries also have some disadvantages, such as the lack of fluidity of solid electrolytes, which makes the solid-solid contact area between the solid electrolyte membrane and the pole piece small, resulting in increased impedance and other problems.

[0053] Based on this, in a first aspect of the present application, a solid electrolyte membrane is provided, wherein the solid electrolyte membrane comprises a lithium-containing solid electrolyte and a composite binder in a mass ratio of (99.2-99.9):(0.1-0.8).

[0054] The composite binder includes a first binder and a second binder; the first binder includes polytetrafluoroethylene.

[0055] The second binder includes polyimide, and the polyimide has a structural unit represented by formula (I): ;

[0056] Wherein, R1 is each independently a single bond, -O-, -C(=O)-, an ester group, , or ; L1, L2 and L3 are each independently an arylene group having 6 to 12 carbon atoms.

[0057] Ring A is selected from the structures represented by formula (A-1) to formula (A-6): , , , , , R2, when it appears each time, is independently H, halogen, alkyl having 1 to 8 carbon atoms, or haloalkyl having 1 to 8 carbon atoms; m is a positive integer greater than or equal to 1. For example, m includes but is not limited to 1, 5, 10, 100, 500, 1000, 3000, 5000, 8000, 10000, 50000, 100000, or 300000.

[0058] The solid electrolyte membrane provided by the present application includes a lithium-containing solid electrolyte and a composite binder in a specific mass ratio, wherein the composite binder includes a first binder and a polyimide second binder of a specific structure. Polar groups such as imide groups contained in polyimide can interact with ions in the lithium-containing solid electrolyte to promote the dissolution and transmission of ions; at the same time, it can also enhance the interfacial bonding force between polyimide and the pole piece, and improve the transmission efficiency of ions at the interface. In addition, the conjugated structure contained in polyimide and the spatial configuration of the functional group can provide a more favorable channel for ion transmission and reduce the resistance to ion transmission.

[0059] Therefore, a polyimide with a specific molecular structure is selected, which can generate a strong intermolecular force between the lithium-containing solid electrolyte and the first binder, thereby improving the viscosity of the solid electrolyte membrane. At the same time, polyimide has certain flexibility, deformability and surface activity, which can better fill and fit the gaps between different materials and improve the interfacial wettability between the solid electrolyte and the electrode material, so as to reduce interfacial voids and defects, increase the interfacial contact area, enhance the bonding effect, enhance the ion transmission efficiency and reduce the transmission impedance. In addition, the polyimide compounded with the first binder can also provide a certain mechanical strength and stability for the solid electrolyte membrane, thereby preventing the solid electrolyte from structural damage or deformation during the charge and discharge process.

[0060] In summary, the solid electrolyte membrane provided in the present application can effectively improve the adhesion between the components of the solid electrolyte membrane and between the components and the electrode sheets by selecting a polyimide with a specific structure, and in combination with a lithium-containing solid electrolyte and a first binder, so as to form a good enhanced interface contact; thereby, it can effectively reduce the impedance of the battery and improve the conductivity.

[0061] It can be understood that in the present application, polyimide having a structural unit shown in formula (I) can be used as the second binder. For example, the source of polyimide includes but is not limited to commercially available, homemade, etc. Further, the corresponding polyimide model includes but is not limited to P406634, P874997.

[0062] It can be understood that in the present application, the mass ratio of the lithium-containing solid electrolyte and the composite binder included in the solid electrolyte membrane can be selected from any value between (99.2-99.9): (0.1-0.8). Further, the mass ratio of the lithium-containing solid electrolyte and the composite binder includes but is not limited to 99.2:0.8, 99.3:0.7, 99.4:0.6, 99.5:0.5, 99.6:0.4, 99.7:0.3, 99.8:0.2 or 99.9:0.1, or within the range of the above two point values.

[0063] The solid electrolyte membrane provided by the present application has a high proportion of lithium-containing solid electrolytes, and a large amount of lithium-containing solid electrolytes provide sufficient migration paths and sites for lithium ions, which is conducive to the rapid migration of lithium ions in the solid electrolyte membrane, thereby ensuring that the battery has good ion conductivity, enabling the battery to efficiently carry out the charge and discharge process, reduce the internal resistance of the battery, and improve the power performance of the battery. In addition, the present application compounds the first binder and the second binder, which can effectively reduce the amount of binder. At this time, a small amount of composite binder can effectively bond the lithium-containing solid electrolyte particles together, and then can effectively prevent the solid electrolyte particles from falling off and displacing during the use of the battery, which is important for maintaining the mechanical properties of the solid electrolyte membrane and allowing it to withstand the mechanical stress and strain inside the battery.

[0064] In one example, R1 is independently -C(=O)- or an ester group, and the A ring is or , R2, when it appears each time, is independently an alkyl group having 1 to 8 carbon atoms or a haloalkyl group having 1 to 8 carbon atoms.

[0065] The A ring is selected from cyclopentyl, which has a relatively compact structure compared to cyclohexyl, and has better matching properties with lithium-containing solid electrolyte particles in size and shape, and is not easy to chemically react with lithium-containing solid electrolytes, electrode materials, etc. during the charge and discharge process of the battery. This helps to maintain the long-term stability and reliability of the solid electrolyte membrane and improve the filling and bonding effects in the solid electrolyte membrane.

[0066] In one example, the polyimide comprises , , , , , , , , , , and One or more of .

[0067] Polytetrafluoroethylene has high mechanical strength and certain flexibility. When used in combination with polyimide, it can form a strong and elastic bonding system in the solid electrolyte membrane to maintain close contact between lithium-containing solid electrolyte particles, ensure that ions can migrate smoothly in the solid electrolyte membrane, improve the efficiency of ion conduction, reduce the internal resistance of the battery, and improve the battery's charge and discharge performance. In addition, when polyimide is used in combination with polytetrafluoroethylene, it can further improve the interface performance between the solid electrolyte membrane and the electrode, reduce the interface resistance and polarization phenomenon, and improve the transmission efficiency of lithium ions at the interface.

[0068] In one example, in the composite adhesive, the mass ratio of the first adhesive to the second adhesive is 1: (0.1-10). It is understandable that the mass ratio of the first adhesive to the second adhesive can be selected from any value between 1: (0.1-10). Further, the mass ratio of the first adhesive to the second adhesive includes but is not limited to 1: 0.1, 1: 0.4, 1: 0.6, 1: 0.8, 1: 1, 1: 1.5, 1: 2, 1: 2.5, 1: 3, 1: 3.5, 1: 4, 1: 4.5, 1: 5, 1: 5.5, 1: 6, 1: 6.5, 1: 7, 1: 7.5, 1: 8, 1: 8.5, 1: 9, 1: 9.5 or 1: 10, or within the range of any two of the above point values.

[0069] In one example, the solid electrolyte membrane includes, by mass percentage: 99.2% to 99.9% of a solid electrolyte, 0.05% to 0.4% of a first binder, and 0.05% to 0.4% of a second binder.

[0070] It is understandable that the mass percentage of the solid electrolyte can be selected from any value between 99.2% and 99.9%. Further, the mass percentage of the solid electrolyte includes but is not limited to 99.2%, 99.3%, 99.5%, 99.6%, 99.7%, 99.8% or 99.9%, or a range consisting of any two of the above point values.

[0071] The mass percentage of the first binder can be selected from any value between 0.05% and 0.4%. Further, the mass percentage of the first binder includes, but is not limited to, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38% or 0.4%, or within the range formed by any two of the above point values.

[0072] The mass percentage of the second binder can be selected from any value between 0.05% and 0.4%. Further, the mass percentage of the second binder includes, but is not limited to, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38% or 0.4%, or within the range formed by any two of the above point values.

[0073] In one example, the lithium-containing solid electrolyte includes one or more of Li n1 PO n2 N n3 and Li3MeCl6;

[0074] where 0 < n1 ≤ 1, 0 < n2 ≤ 1, 0 < n3 ≤ 1; Me includes one or more of In, Y, Sc, Ta, Zr, Yb and Ho.

[0075] The value of n1 includes, but is not limited to, 0.1, 0.3, 0.5, 0.7, 0.8, 0.9 or 1. The value of n2 includes, but is not limited to, 0.1, 0.3, 0.5, 0.7, 0.8, 0.9 or 1. The value of n3 includes, but is not limited to, 0.1, 0.3, 0.5, 0.7, 0.8, 0.9 or 1.

[0076] In one example, the lithium-containing solid electrolyte includes one or more of Li3InCl6, Li3YCl6, Li3ScCl6, Li3TaCl6, Li3ZrCl6, Li3YbCl6 and Li3HoCl6.

[0077] Furthermore, the lithium-containing solid electrolyte is Li3InCl6. The compound use of Li3InCl6, the first binder and the second binder can maintain effective adhesion to the electrode material when the charge and discharge volume of Li3InCl6 changes, and maintain the integrity of the electrode structure. At this time, it can not only ensure the correct electron transmission path inside the electrode, but also avoid energy loss caused by electron transmission in unnecessary places.

[0078] In one example, the thickness of the solid electrolyte membrane is 15µm to 200µm. Further, the thickness of the solid electrolyte membrane includes but is not limited to 15µm, 20µm, 25µm, 30µm, 35µm, 40µm, 45µm, 50µm, 60µm, 70µm, 80µm, 90µm, 100µm, 120µm, 140µm, 150µm, 160µm, 170µm, 180µm, 190µm or 200µm.

[0079] A solid electrolyte membrane of suitable thickness can better maintain a stable interface between the electrode and the electrolyte, reduce the generation of interface resistance and polarization. This helps to improve the cycle performance of the battery and extend the service life of the battery. Preferably, the thickness of the solid electrolyte membrane is 15µm to 50µm.

[0080] Since solid-state batteries do not have electrolytes, they can effectively solve the safety problem of batteries. Therefore, solid-state lithium batteries have become a research hotspot in the current industry. However, the traditional method of preparing electrolyte membranes requires the use of solvents, dispersants and plasticizers, which are harmful to the electrolyte itself and reduce ionic conductivity, seriously hindering the commercialization of all-solid-state batteries.

[0081] The dry film preparation process does not use any solvents, and the solid electrolyte membrane prepared by the dry method can inhibit interfacial reactions, making it a promising preparation method. In the solid electrolyte membrane prepared by the traditional dry method, the capacity of lithium ions is limited, and due to the limited viscoelasticity, sufficient interfacial adhesion between the active material, solid electrolyte and conductive carbon cannot be guaranteed. This causes microcracks in the electrolyte during the battery charging and discharging process, causing micro short circuits and a decrease in battery capacity / cycle stability.

[0082] A second aspect of the present application provides a method for preparing a solid electrolyte membrane according to any one of the first aspects of the present application, comprising the following steps:

[0083] The lithium-containing solid electrolyte and the composite binder are mixed and pressed to prepare the solid electrolyte membrane.

[0084] In one example, in the composite binder, the mass ratio of the first binder to the second binder is 1:(0.1-10).

[0085] In one example, the mixing process parameters include: a mixing temperature of 30° C. to 100° C. It is understandable that the mixing temperature includes but is not limited to 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C., or a range formed by any two of the above point values.

[0086] In order to shorten the mixing time and improve the mixing efficiency, the mixing process parameters further include: the mixing temperature is 60°C to 80°C.

[0087] In one example, the pressing process parameters include: a pressing temperature of 20°C to 200°C.

[0088] Furthermore, the pressing process parameters include: performing a first pressing treatment at 50°C to 200°C, and performing a second pressing treatment at 20°C to 120°C.

[0089] It is understandable that in the present application, the method for performing the pressing treatment can be selected from the common methods of those skilled in the art. For example, the method for performing the pressing treatment includes but is not limited to hot roller pressing. The temperature for performing the first pressing treatment includes but is not limited to 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, or within the range of any two of the above point values. The temperature for performing the second pressing treatment includes but is not limited to 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or within the range of any two of the above point values.

[0090] Furthermore, the pressure of the first pressing process is 5t to 40t. It can be understood that in the present application, the pressure of the first pressing process includes but is not limited to 5t, 10t, 15t, 20t, 25t, 30t, 35t, 38t or 40t, or a range formed by any two of the above point values.

[0091] Furthermore, the pressure of the second pressing process is 5t to 40t. It can be understood that in the present application, the pressure of the second pressing process includes but is not limited to 5t, 10t, 15t, 20t, 25t, 30t, 35t, 38t or 40t, or a range formed by any two of the above point values.

[0092] In one example, the raw materials for preparing the solid electrolyte membrane do not include a solvent.

[0093] In one example, the raw materials for preparing the solid electrolyte membrane do not include a plasticizer.

[0094] According to a third aspect of the present application, a solid-state battery is provided, comprising a positive electrode, a negative electrode, and an electrolyte membrane disposed between the positive electrode and the negative electrode, wherein the electrolyte membrane is the solid-state electrolyte membrane described in any example of the first aspect of the present application.

[0095] The positive electrode at least includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.

[0096] Wherein, the positive electrode active material is selected from at least one of lithium-rich manganese-based, positive electrode ternary materials, lithium iron phosphate and lithium cobalt oxide. For example, the positive electrode ternary materials include but are not limited to lithium nickel cobalt manganese oxide [NCM (111, 333, 523, 622, 613, 811)], or lithium nickel cobalt aluminum oxide (NCA). The positive electrode conductive agent is selected from one or more of carbon black, carbon nanotubes, conductive fibers, Ketjen black, graphene and conductive graphite. The positive electrode binder is independently selected from one or more of polytetrafluoroethylene and polyvinylidene fluoride.

[0097] The negative electrode at least includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.

[0098] The negative electrode active material is selected from one or more of graphite, silicon oxide, lithium titanate and metallic lithium. The negative electrode conductive agent is selected from one or more of carbon black, carbon nanotubes, conductive fibers, Ketjen black, graphene and conductive graphite. The negative electrode binder is independently selected from one or more of polytetrafluoroethylene and polyvinylidene fluoride.

[0099] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0100] [Polyimide]

[0101] Polyimide A1: CAS: 62929-02-6, model: P406634, purchased from: Aladdin, structure: ;

[0102] Polyimide A2: In a 250mL three-necked flask equipped with a nitrogen inlet, a short-path distillation head with a receiving flask and a nitrogen outlet, and a mechanical stirrer, put: 1,2-diaminoethane (17.5mmol, 1eq) and m-cresol (20mL), and place it under a nitrogen atmosphere for 5 minutes. Then add all the hexafluorodianhydride 6-FDA (7.781g, 17.5mmol, 1eq) to the flask at once and rinse with m-cresol (20mL). The mixture was stirred at room temperature for 1 hour, then slowly heated to 180°C and stirred for 2 days. After 2 days, the reaction was cooled and the polymer was separated by precipitation in methanol. The white fibrous polymer was washed several times with hot methanol and dried under reduced pressure at 120°C overnight to prepare polyimide A2. The structure of polyimide A2 is .

[0103] Example 1

[0104] A lithium-containing solid electrolyte (Li3InCl6) with a mass percentage of 99.8% and a composite binder with a mass percentage of 0.2% were mixed, wherein the composite binder included 0.16% polytetrafluoroethylene PTFE and 0.04% polyimide A1 by mass, and then heated and ground in a mortar at 80°C, followed by a first roll-pressing film-forming treatment at 80°C and 25t, and then a second roll-pressing thinning treatment at 60°C and 30t to obtain a 50µm dry electrolyte membrane. The actual picture of the dry electrolyte membrane prepared in Example 1 is shown in FIG. Figure 2 (a) shown.

[0105] Example 2

[0106] A lithium-containing solid electrolyte (Li3InCl6) with a mass percentage of 99.8% and a composite binder with a mass percentage of 0.2% were mixed, wherein the composite binder included 0.1% of polytetrafluoroethylene PTFE with a mass percentage and 0.1% of polyimide A1 with a mass percentage. The mixture was heated and ground in a mortar at 80°C, and then subjected to a first roll-pressing film-forming treatment at 80°C and 25t, and then subjected to a second roll-pressing thinning treatment at 60°C and 30t to obtain a 50µm dry electrolyte membrane.

[0107] Example 3

[0108] A lithium-containing solid electrolyte (Li3InCl6) with a mass percentage of 99.8% and a composite binder with a mass percentage of 0.2% were mixed, wherein the composite binder included 0.05% of polytetrafluoroethylene PTFE and 0.15% of polyimide A1, and then heated and ground in a mortar at 80°C, and then subjected to a first roll-pressing film-forming treatment at 80°C and 25t, and then subjected to a second roll-pressing thinning treatment at 60°C and 30t to obtain a 50µm dry electrolyte membrane.

[0109] Comparative Example 1

[0110] A lithium-containing solid electrolyte (Li3InCl6) with a mass percentage of 99.8% and polytetrafluoroethylene PTFE with a mass percentage of 0.2% were mixed, heated and ground in a mortar at 80°C, and then subjected to a first roll-pressing film-forming treatment at 80°C and 25t, and then a second roll-pressing thinning treatment was performed at 60°C and 30t to obtain a 50µm dry electrolyte membrane.

[0111] Comparative Example 2

[0112] A lithium-containing solid electrolyte (Li3InCl6) with a mass percentage of 99% and a composite binder with a mass percentage of 1% were mixed, wherein the composite binder included 0.8% of polytetrafluoroethylene PTFE and 0.1% of polyimide A1 by mass, and then heated and ground in a mortar at 80°C, and then subjected to a first roll-pressing film-forming treatment at 80°C and 25t, and then subjected to a second roll-pressing thinning treatment at 60°C and 30t to obtain a 50µm dry electrolyte membrane.

[0113] Comparative Example 3

[0114] A 99.8% lithium-containing solid electrolyte (Li3InCl6) and a 0.2% composite binder were mixed, wherein the composite binder included 0.16% polytetrafluoroethylene PTFE and 0.04% polyimide A2, heated and ground in a mortar at 80°C, then subjected to a first roll-pressing film-forming treatment at 80°C and 25t, and then subjected to a second roll-pressing thinning treatment at 60°C and 30t. The resulting dry electrolyte could not form a flexible film. The actual picture of the dry electrolyte membrane prepared in Comparative Example 3 is shown in FIG. Figure 2 (b) shown.

[0115] The ionic conductivity and mechanical adsorption strength of the dry electrolyte membranes of the test examples and comparative examples were tested, and the corresponding test results are shown in Table 1. The dry electrolyte membranes of Example 1, Comparative Example 1 and Comparative Example 2 were assembled into solid-state batteries with commercial lithium iron phosphate positive electrodes and graphite negative electrodes, and the solid-state battery was tested for the first week full charge state impedance test. The corresponding test results are shown in Table 1. Figure 1 shown.

[0116] Table 1

[0117]

[0118] From the comparison between the embodiments and the comparative examples in Table 1, it can be seen that the ionic conductivity of embodiment 1 is the highest and its mechanical adsorption strength is relatively high, indicating that the amount of polyimide added at this time is the optimal ratio. The ionic conductivity of comparative example 1 is less than that of each embodiment and its mechanical adsorption strength is the lowest, indicating that the addition of polyimide as the second binder significantly improves the ionic conductivity of the solid electrolyte. The ionic conductivity of comparative example 2 is relatively low, but its mechanical adsorption strength is the highest, indicating that excessive addition of binder will reduce the ionic conductivity and increase the mechanical properties of the electrolyte membrane. In comparative example 3, the second binder is polyimide A2 of other structures. At this time, the dry electrolyte obtained cannot form a flexible membrane; and its ionic conductivity and mechanical strength are both the lowest.

[0119] In addition. Figure 1It can be seen that the impedance of comparative example 2 is the largest, the impedance of comparative example 1 is relatively low, and the impedance of embodiment 1 is the lowest, which proves that the interface contact of the solid electrolyte membrane prepared in embodiment 1 is better.

[0120] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0121] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A solid electrolyte membrane, characterized in that: Comprising a lithium-containing solid electrolyte and a composite binder with a mass ratio of (99.2 to 99.9):(0.1 to 0.8); The composite binder comprises a first binder and a second binder; the first binder comprises polytetrafluoroethylene; The second binder includes polyimide, and the polyimide has a structural unit represented by formula (I): ; Wherein, R1 is each independently a single bond, -O-, -C(=O)-, an ester group, , or ; L1, L2 and L3 are each independently an arylene group having 6 to 12 carbon atoms; Ring A is selected from the structures represented by formula (A-1) to formula (A-6): , , , , , ; R2, when it appears each time, is independently H, halogen, alkyl having 1 to 8 carbon atoms, or haloalkyl having 1 to 8 carbon atoms; m is a positive integer greater than or equal to 1.

2. The solid electrolyte membrane according to claim 1, characterized in that R1 is independently -C(=O)- or an ester group, and the A ring is or , R2, when it appears each time, is independently an alkyl group having 1 to 8 carbon atoms or a haloalkyl group having 1 to 8 carbon atoms.

3. The solid electrolyte membrane according to claim 1, characterized in that The polyimide comprises , , , , , , , , , , and One or more of .

4. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The solid electrolyte membrane has one or more of the following characteristics: (1) In the composite binder, the mass ratio of the first binder to the second binder is 1:(0.1 to 10); (2) By mass percentage, the solid electrolyte membrane comprises: 99.2% to 99.9% of a solid electrolyte, 0.05% to 0.4% of the first binder, and 0.05% to 0.4% of the second binder.

5. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The lithium-containing solid electrolyte includes Li n1 PO n2 N n3 and one or more of Li3MeCl6; Wherein, 0 < n1 ≤ 1, 0 < n2 ≤ 1, 0 < n3 ≤ 1; Me comprises one or more of In, Y, Sc, Ta, Zr, Yb, and Ho.

6. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The thickness of the solid electrolyte membrane is 15 µm to 200 µm.

7. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: Comprising the following steps: Mix the lithium-containing solid electrolyte and the composite binder, and after pressing, prepare the solid electrolyte membrane.

8. The method for preparing a solid electrolyte membrane according to claim 7, characterized in that: The preparation method has one or more of the following characteristics: (1) The process parameters of the mixing include: the mixing temperature is 30°C to 100°C; (2) The process parameters of the pressing include: the pressing temperature is 20°C to 200°C.

9. A solid-state battery, characterized in that: Comprising a positive electrode, a negative electrode, and an electrolyte membrane disposed between the positive electrode and the negative electrode, and the electrolyte membrane is the solid electrolyte membrane according to any one of claims 1 to 6.

10. An electrical device, characterized in that: Comprising the solid-state battery according to claim 9.